Infection control policies in Brazil and quality of nursing care: necessary reflections (Research, Society and Development, 2020)
The objective was to reflect on the infection control policies related to health care in Brazil and the quality of nursing care in infection control from the theoretical perspective of Donabedian. This is a reflection based on the Health Care-Related Infection Control Policies in Brazil and on the theoretical Avedis Donabedian. The reflections point out that the infection control policies related to healthcare in Brazil and the quality of nursing care favor healthcare. It is concluded through the findings of the study on the quality of nursing care associated with the control of infections related to health care from the theoretical perspective of Avedis Donabedian that nurses are the main actor in the process of managing care in the IRAS and that government programs aimed at controlling and preventing these in force in Brazil preach the culture of safe assistance in health services.